Challenges of Latino Aging in the Americas - Vega, W.A (Springer, 2015)
This book examines one of the most important demographic changes facing the United States: an overall aging population and the increasing influence of Latinos. It also looks at the changing demographics in Mexico and its impact on the health and financial well-being of aging Mexicans and Mexican Americans. The book provides a conceptual and accessible framework that will educate and inform readers about the interconnectedness of the demographic trends facing these two countries. It also explores the ultimate personal, social, and political impact they will have on all Americans, in the U.S. as well as Mexico.